Case Report: An Undefined Liver Lesion in a Young Man With Severe Aplastic Anemia: A Teachable Moment - Liu, Jin; Sui, Jidong; Sun, Deguang; Guo, Kun; Gao, Zhenming; Bian, Jie; Yan, Jinsong; Wang, Liming (Frontiers in Surgery, 2021)
Abstract In this work, we reported a young man with complained of ultrasound showing an undefined liver lesion with asthenia, intermittent fever. Facing the patient’s situation with severe agranulocytosis, anemia and thrombocytopenia, we passed through a tough diagnostic process for choosing an appropriate treatment for him with an ambiguous result of pathological biopsy. The undefined liver lesion was successfully solved by withdrawing the androgen for observation, without lobectomy. The lesion diminished gradually for two years follow-up.